2005
DOI: 10.1073/pnas.0508392103
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a nitroimidazo-oxazine-specific protein involved in PA-824 resistance in Mycobacterium tuberculosis

Abstract: PA-824 is a promising new compound for the treatment of tuberculosis that is currently undergoing human trials. Like its progenitors metronidazole and CGI-17341, PA-824 is a prodrug of the nitroimidazole class, requiring bioreductive activation of an aromatic nitro group to exert an antitubercular effect. We have confirmed that resistance to PA-824 (a nitroimidazo-oxazine) and CGI-17341 (a nitroimidazo-oxazole) is most commonly mediated by loss of a specific glucose-6-phosphate dehydrogenase (FGD1) or its deaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
281
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 311 publications
(291 citation statements)
references
References 32 publications
(33 reference statements)
10
281
0
Order By: Relevance
“…Spontaneously arising PDIM-deficient variants have been described previously (1,7,8,11,15,(19)(20)(21) and are probably more common than has been reported or realized. Although spontaneous PDIM deficiency has most frequently been associated with the H37Rv strain, it has also recently been described for the M. tuberculosis Erdman strain and the clinical isolate HN878 (7,20).…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneously arising PDIM-deficient variants have been described previously (1,7,8,11,15,(19)(20)(21) and are probably more common than has been reported or realized. Although spontaneous PDIM deficiency has most frequently been associated with the H37Rv strain, it has also recently been described for the M. tuberculosis Erdman strain and the clinical isolate HN878 (7,20).…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy in complementation led us to investigate whether the attenuation of the complemented strains might be due to a deficiency of the cell wall-associated lipid phthiocerol dimycocerosate (PDIM). Loss of PDIM results in impaired replication of Mtb in mouse lungs (24,25), and mutations that abolish synthesis of this lipid have been show to occur spontaneously (26)(27)(28). Lipid profile analysis revealed that both WT and ΔpckA strains expressed similar levels of PDIM.…”
Section: Pepck Is Essential For Growth and Survival Of Mtb During Botmentioning
confidence: 99%
“…The reduction of these compounds is probably mediated by the nitroreductase Rv3547 as mutants lacking this enzyme (H37Rv-T2) are also cross-resistant. 16 The MAC (minimum anaerobicidal concentration) values for compounds 4-6 were equivalent. 30…”
mentioning
confidence: 97%
“…14,15 Prior work has shown that PA-824 acts as a prodrug requiring bioreductive activation before exerting its biological effect. 16 One serious issue with the clinical use of both PA-824 and OPC-67683 lies in their low water solubility. PA-824 is only soluble at 10.2μg/mL 17 (Table 1) and the in vivo activity of OPC-67683 requires formulation in 5% gum arabic.…”
mentioning
confidence: 99%